Peran Iklan Media Sosial, Brand Image, dan Inovasi Produk untuk Membangun Loyalitas Konsumen Kalbe Nutritionals di Daerah Istimewa Yogyakarta - Nita Dwi Setiawati; Andriya Risdwiyanto (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study examines the influence of social media advertising, brand image, and product innovation on consumer loyalty toward Kalbe Nutritional in Yogyakarta, both partially and simultaneously. Using a quantitative method with purposive sampling, data were collected from 100 respondents through a Likert-scale questionnaire and analyzed using SPSS 20. The results indicate that social media advertising and brand image do not have a significant effect on consumer loyalty, while product innovation has a positive and significant impact. The limitation of this study lies in the absence of age segmentation. This study recommends strengthening digital strategies and conducting further research that considers demographic factors